Interactions, structure and properties in poly(lactic acid)/thermoplastic polymer blends - B. Imre; K. Renner; B. Pukanszky (eXPRESS Polymer Letters)
Blends were prepared from poly(lactic acid) (PLA) and three thermoplastics, polystyrene (PS), polycarbonate (PC) and poly(methyl methacrylate) (PMMA). Rheological and mechanical properties, structure and component interactions were determined by various methods. The results showed that the structure and properties of the blends cover a relatively wide range. All three blends have heterogeneous structure, but the size of the dispersed particles differs by an order of magnitude indicating dissimilar interactions for the corresponding pairs. Properties change accordingly, the blend containing the smallest dispersed particles has the largest tensile strength, while PLA/PS blends with the coarsest structure have the smallest. The latter blends are also very brittle. Component interactions were estimated by four different methods, the determination of the size of the dispersed particles, the calculation of the Flory-Huggins interaction parameter from solvent absorption, from solubility parameters, and by the quantitative evaluation of the composition dependence of tensile strength. All approaches led to the same result indicating strong interaction for the PLA/PMMA pair and weak for PLA and PS. A general correlation was established between interactions and the mechanical properties of the blends.